A fertile future: Fertility preservation special series - Rod T Mitchell; Suzannah A Williams (Bioscientifica, 2022)
Fertility preservation is a rapidly advancing field with numerous broad applications ranging from retaining the prospect of fertility in a child with cancer to protecting an entire species from extinction. In recent years, huge strides have been made in understanding the biology of male and female reproduction in animals and humans and using this knowledge to develop strategies for fertility preservation across a range of clinical and ecological applications. This Reproduction and Fertility preservation series is composed of articles from experts on this topic and these will highlight key developments in fertility preservation and also identify the challenges that still face this exciting and relatively new field.